The Impact of Christian Leadership on PT. Indocement Tunggal Prakarsa Tbk - Tony Tedjo; Gunawan Simondinata; Aneke Maukar; Harry Ciawi (Green Publisher Indonesia, 2023)
Leaders play a vital role in a company. The success or failure of a company is greatly influenced by the leadership style adopted in the Company. This research is field research with a qualitative approach. The method used in this study is the method of interviews and observation or observation. Harmony occurred between the Company and the assisted villages around the cement factory of PT Indocement Tunggal Prakarsa Tbk. Palimanan unit, which in the previous era of Leadership did not occur within the scope of the CSR program. The changes that have occurred and can be seen are the increasing relations with the assisted villages within the assisted area of P.T. Indocement Tunggal Prakarsa. Tbk Palimanan unit, and the maximum reactivation of UPS (Waste Management Unit) BUMDes (Village Owned Enterprises) West Palimanan. Combining the Democratic Leadership Style and Christian Leadership is applied to solve existing problems. Success in the era of Christian Leadership in PT Indocement Tunggal Prakarsa Tbk. is inseparable from divine Influence, namely the factor of God's intervention in an individual's life. God's intervention aims to shape the individual into a leader with full capacity by using self, other people, special events, and the individual leader's response to what she is experiencing.